Effects of Unilateral Nephrectomy on Renal Function in Male Spontaneously Diabetic Torii Fatty Rats: A Novel Obese Type 2 Diabetic Model - Yoshiaki Katsuda; Yusuke Kemmochi; Mimi Maki; Ryuhei Sano; Yasufumi Toriniwa; Yukihito Ishii; Katsuhiro Miyajima; Kochi Kakimoto; Takeshi Ohta (Journal of Diabetes Research)
The Spontaneously Diabetic Torii (SDT) fatty rat is a new model for obese type 2 diabetes. The aim of the present study was to investigate the effect of 1/2 nephrectomy (Nx) on renal function and morphology and on blood pressure in SDT fatty rats. Male SDT fatty rats underwent 1/2 Nx or a sham operation (Sham). Subsequently, animals were studied with respect to renal function and histological alterations. Induction of 1/2 Nx in SDT fatty rats led to functional and morphological damage to the remnant kidney and to hypertension, which are considered main characteristics of chronic kidney disease, at a younger age compared with the sham group. In conclusion, the SDT fatty rat is useful in investigations to elucidate the pathogenesis of human diabetic nephropathy and in new drug discovery.